Drug Court Recidivism in the Rural Midwest: A 3-Year Post-Separation Analysis. (July 2021) - Wadkins, Theresa; Campbell, Julie
Substance abuse continues to be a pressing social problem in the United States today. As the country battles an opioid epidemic, many jurisdictions have adopted the problem-solving court model in response. These specialized courts, known as drug courts, offer a rehabilitative approach to offender management. Drug courts balance substance abuse rehabilitation with community-based supervision and operate with the philosophy that addressing the addiction will result in a decrease in criminal offending. The current study examines the recidivism rates for 50 participants who have been separated (i.e., completed or terminated) from one rural drug court program in the Midwest for at least 3 years. Findings indicate that successful completion of drug court is associated with decreases in misdemeanor offending, and more importantly, decreases in felony offending. While preliminary, the findings of this research provide support for the drug court model in the rural Midwest. Further research in this area is highly recommended.